Regional differences in the care and outcomes of acute stroke patients in Australia: an observational study using evidence from the Australian Stroke Clinical Registry (AuSCR) - Joosup Kim; Dominique A Cadilhac; Richard White; Natasha A Lannin; Fiona Ryan; Karen Ford; Mitchell Dwyer; Karen Francis; Gregory M Peterson; Seana Gall; Hoang Phan; Helen Castley; et al. (BMJ Open)
Objective To compare the processes and outcomes of care in patients who had a stroke treated in urban versus rural hospitals in Australia.Design Observational study using data from a multicentre national registry.Setting Data from 50 acute care hospitals in Australia (25 urban, 25 rural) which participated in the Australian Stroke Clinical Registry during the period 2010–2015.Participants Patients were divided into two groups (urban, rural) according to the Australian Standard Geographical Classification Remoteness Area classification. Data pertaining to 28 115 patients who had a stroke were analysed, of whom 8159 (29%) were admitted to hospitals located within rural areas.Primary and secondary outcome measures Regional differences in processes of care (admission to a stroke unit, thrombolysis for ischaemic stroke, discharge on antihypertensive medication and provision of a care plan), and survival analyses up to 180 days and health-related quality of life at 90–180 days.Results Compared with those admitted to urban hospitals, patients in rural hospitals less often received thrombolysis (urban 12.7% vs rural 7.5%, p<0.001) or received treatment in stroke units (urban 82.2% vs rural 76.5%, p<0.001), and fewer were discharged with a care plan (urban 61.3% vs rural 44.7%, p<0.001). No significant differences were found in terms of survival or overall self-reported quality of life.Conclusions Rural access to recommended components of acute stroke care was comparatively poorer; however, this did not appear to impact health outcomes at approximately 6 months.